Menyelidiki Hukum Pertanggungjawaban Pidana Partai Politik Terkait Tindak Pidana Korupsi - Moh. Fahri; Moh. Rusdiyanto U. Puluhulawa (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The aim of this research is to find out criminal responsibility for political parties based on the perspective of responsibility theory and to find out the ideal sanctions for political parties that obtain funds from corruption. The research method used in this research is literature or normative, namely